Agile Governance dalam Pembangunan Zona Integritas di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau - Evi Nadhifah Prihatini; Mayarni Mayarni; Hasim As’ari (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This study examines the implementation of Agile Governance in the development of the Integrity Zone at the Faculty of Social and Political Sciences, Universitas Riau. The study is motivated by the need for adaptive, responsive, and participatory governance to support bureaucratic reform and improve public service quality in higher education institutions. Despite ongoing efforts, the development of the Integrity Zone still faces challenges, including limited human resources, budget and facility constraints, inefficient administrative systems, and suboptimal digital service integration.This research employed a qualitative descriptive approach through observation, in-depth interviews, and documentation involving faculty leaders, the Integrity Zone team, educational staff, students, and alumni. The findings show that Agile Governance has been implemented through six indicators: good enough governance, business-driven, human-focused, quick wins, systematic and adaptive approach, and simple design and continuous refinement. Its implementation is reflected in administrative service digitalization, WhatsApp helpdesk services, consultation corners, the Complaint, Assistance, and Health Support Unit (P2K), service satisfaction surveys, integrity culture strengthening, and simplified service procedures. However, implementation remains uneven due to limited resources, inadequate digital integration, and organizational culture challenges. The study recommends strengthening digital service integration, enhancing human resource capacity, applying data-based service evaluations, and improving coordination and organizational culture to ensure sustainable and effective Integrity Zone development.